The progress of research on vacancies in HMF electrooxidation - Chen, Zhikai; Zhang, Gan; Jiang, Jinxia; Feng, Xin; Li, Wei; Xiang, Xiaohong; Linling, Gan (Frontiers in Chemistry, 2024)
5-Hydroxymethylfurfural (HMF), serving as a versatile platform compound bridging biomass resource and the fine chemicals industry, holds significant importance in biomass conversion processes. The electrooxidation of HMF plays a crucial role in yielding the valuable product (2,5-furandicarboxylic acid), which finds important applications in antimicrobial agents, pharmaceutical intermediates, polyester synthesis, and so on. Defect engineering stands as one of the most effective strategies for precisely synthesizing electrocatalytic materials, which could tune the electronic structure and coordination environment, and further altering the adsorption energy of HMF intermediate species, consequently increasing the kinetics of HMF electrooxidation. Thereinto, the most routine and effective defect are the anionic vacancies and cationic vacancies. In this concise review, the catalytic reaction mechanism for selective HMF oxidation is first elucidated, with a focus on the synthesis strategies involving both anionic and cationic vacancies. Recent advancements in various catalytic oxidation systems for HMF are summarized and synthesized from this perspective. Finally, the future research prospects for selective HMF oxidation are discussed.